Climate risk country profile Kazakhstan. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This publication synthesizes climate characteristics and projections, vulnerability to natural hazards, sectoral climate change impacts, and adaptation priorities in Kazakhstan.
Keywords: Economic development; Sustainable development; Economic development -- Environmental aspects -- Kazakhstan; Climate change; Electronic book